2013
DOI: 10.1162/jocn_a_00388
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Individual and Joint Action Outcomes in Duet Music Performance

Abstract: Abstract■ We investigated whether people monitor the outcomes of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 71 publications
7
105
0
2
Order By: Relevance
“…Kourtis et al, 2014;Meyer et al, 2013;Tsai et al, 2011;Vesper et al, 2013). For example, Loehr et al (2013) showed that pianists playing chords together distinguish errors which affect a pianist's own part only from errors which affect the harmony of the chord and so result in failure to achieve a collective goal. Richardson, Marsh, and Baron (2007) showed that acting together with another rather than alone can modulate how an individual grasps an object.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kourtis et al, 2014;Meyer et al, 2013;Tsai et al, 2011;Vesper et al, 2013). For example, Loehr et al (2013) showed that pianists playing chords together distinguish errors which affect a pianist's own part only from errors which affect the harmony of the chord and so result in failure to achieve a collective goal. Richardson, Marsh, and Baron (2007) showed that acting together with another rather than alone can modulate how an individual grasps an object.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings indicate that in joint actions such as playing a piano duet, clinking glasses, jumping together and moving an object, agents' motor representations and processes take into account relations between their own actions and others' in preparing and monitoring their actions (Kourtis, Knoblich, Wozniak, & Sebanz, 2014;Loehr et al, 2013;Meyer, van der Wel, & Hunnius, 2013;Tsai, Sebanz, & Knoblich, 2011;Vesper, van der Wel, Knoblich, & Sebanz, 2013). These findings motivated us to conjecture that participants in joint actions can represent collective goals motorically.…”
Section: Introductionmentioning
confidence: 99%
“…In a parallel vein, an EEG study [97] explored the representation of self and other during rhythmic joint action using a similar piano performance task to the one described above [91]. Pairs of pianists practiced each other's parts prior to the experiment, and then played the left-and right-hand part, respectively, while EEG was recorded.…”
Section: (A) Representing Self and Other In The Brainmentioning
confidence: 99%
“…Producing and learning music likely involves even greater EF demands. For example, music is most often played in coordination with others (Palmer, 2013), which requires switching between multiple auditory streams (Loehr, Kourtis, Vesper, Sebanz, & Knoblich, 2013) and adjusting to other performers (e.g., Loehr & Palmer, 2011;Moore & Chen, 2010). Thus music performance may be associated with relatively general switching advantages, and musicians have indeed been found to outperform non-musicians on switching tasks (Hanna-Pladdy & MacKay, 2011;Moradzadeh, Blumenthal, & Wiseheart, 2014; see also Bugos, Perlstein, McCrae, Brophy, & Bedenbaugh, 2007;Zuk, Benjamin, Kenyon, & Gaab, 2014).…”
Section: Introductionmentioning
confidence: 99%